FIRE GAIETY RETOOLING. - Thoreson, Karen; Svara, James (Public Management (00333611))
The article discusses the move of Oakland Park Fire Rescue Department to use strategic management and a collaborative labor-management-citizen process to engage the stakeholders in the development of response programs in Florida. It states that the citizens demand fire protection and related protective services provided by the local governments. In this regard, the local governments employ the strategy to heighten life safety services and enhance the quality of service.